Pengembangan Manajemen Pariwisata Berkelanjutan Bagi Kelompok Karang Taruna Desa Warnasari Kecamatanpengalengan Kabupaten Bandung - Ade Priangani; Dewi Astuti Mudji; Shylvia Windary (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2020)
The Warnasari Village Tourism Area is a place that offers the attraction of natural scenery and stretches of plantations. The Warnasari Village Tourism Area is projected by the Bandung Regency Culture and Tourism Office as one of the leading tourist destinations in South Bandung. The purpose of this activity is to improve the ability of the Management Team of the Warnasari Tourism Village in terms of managing their products actively and independently and increasing the ability to compile and manage tour packages. Activities carried out for 3 months. Methods of using training. The target of the activity is Karang Taruna, the manager of the attractions of Warnasari Village, amounting to 30 people. The results of this activity have had a positive impact with the implementation of tourist training activities resulting in an increase in the management of tourist attractions and the increased ability to compile and manage tour packages